International Spillovers of Quality Regulations - Luca Macedoni; Ariel Weinberger (CESifo GmbH, 2024)
This paper investigates the positive international spillover effects of non-discriminatory product regulations, such as quality standards. We incorporate regulations into a multi-country general equilibrium framework with firm heterogeneity and variable markups. We model regulations as a fixed cost that any firm selling to an economy must pay, consistent with stylized facts that we present. We demonstrate that in the presence of variable markups, the fixed cost generates a positive spillover on the rest of the world as it induces entry of high-quality firms, and it improves the terms of trade of the non-imposing countries. We argue that the benefits of such regulations are not fully realized under non-cooperative policy settings, leading to a call for international cooperation in setting regulations. We estimate our model to quantify the effects of regulations on consumers' welfare, the extent of the positive externalities across countries, the relative importance of the entry of high-quality firms and of the terms of trade effect of regulations, and the value of cooperation.
Keywords: F12; F13; L11; 330; allocative efficiency; international spillover; quality standards; variable markups; trade policy